THE DEVELOPMENT OF PROJECT BASED LEARNING E-MODULE ABOUT STRUCTURE AND FUNCTION OF LIVING CREATURES TOPIC - Monica, Friscilia; Putri, Rahmah Evita; Putri, Azza Nuzullah; Arif, Khairil (SEMESTA: Journal of Science Education and Teaching, 2024)
The general background of this research is the limited teaching materials equipped with project-based learning assessment instruments as recommended in Kurikulum Merdeka. The purpose of this research is to produce a Project Based Learning (PjBL) based e-module on the structure and function of living creatures topic that is valid, practical and effective.The type of research used is Research and Development (R&D) with 4-D model’s consisting of the stages of defining, designing, developing and disseminating. However, this research was only untill the development stage due to time constraints. The research instruments consist of teacher questionnaires, student questionnaires, validity test questionnaires, practicality test questionnaires, and effectiveness test questionnaires. The data obtained was analyzed using a formula to analyze the results of validity, practicality and effectiveness tests. The research results show that the PjBL-based e-module developed is valid with an average 88%. The level of practicality is practical with an average 88%. The level of effectiveness is effective which is 84% ​​on average. Based on the research results, it can be concluded that the PjBL-based science learning e-module on the material Structure and Function of the Body of Living Creatures meets the valid, practical and effective categories.